The Early Detection in Gestational Diabetes Mellitus at Indonesia Primary Health Care - Erni Rosita Dewi1, Budi Prasetyo2, Muhammad Ardian Cahya Laksana2, Hermanto Tri Joewono2, Ivon Diah (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Gestational diabetes mellitus (GDM) is diabetes that is first diagnosed during pregnancy. Uncontrolled GDM or late found can increase mortality for both mother and baby. Not only bad medical conditions, but also it can decline the community productivity, affect socio-economic and increasing financial health. Early detection of GDM is crucial to be implemented by providers, especially in the primary health care. Objective: to determine the framework of early detection in gestational diabetes mellitus at primary health care Methods: The method used is a literature review, which was published in 2008-2018. The literature were collected using some keywords such as “detection”, “gestational diabetes mellitus”, and “primary health care” using PubMed and another electronic journal website. Furthermore, the findings were filtered based on our inclusion criteria and analyzed qualitatively. Results: Early detection of GDM in primary health care with risk factor assessment (age of pregnant women ? 35 years, some of bad history namely GDM in previous pregnancies, anti-diabetic drug use, diabetes mellitus in the family, congenital of infants, IUFD, preeclampsia, macrosomia, blood pressure examination, calculation of body mass index and random blood sugar examination). Furthermore, early detection of GDM is carried out by examining blood glucose accompanied by the provision of appropriate glucose solution interventions (OGCT and OGTT). Conclusion: primary health care can take more action in early detection of GDM through quality antenatal care, which can be done by applying the framework of early detection in gestational diabetes mellitus.